A constituição do personagem privilegiado pelo meio jurídico em contos de Machado de Assis - (:unkn) unknown (Universidade Federal de Goiás, 2016)
In dealing with the reading of the Machadian short stories, some recurring features do not cease to be noticed. Among of a series of contexts that are worth mentioning, we notice, for example, that the author chooses scenarios with the presence of characters usually privileged by the legal environment or that, at least, are graduates. In this sense, the reader of Machado de Assis is naturally exposed to plural themes and knowledge that involve Law. On account of all this, in order to perform a research on the construction of this character in certain literary creations of the writer, three short stories were selected: "Virginius (narrative de um advogado)", "Ex Cathedra" and "Suje-se Gordo!". Some of these narratives even address the way the labors were solved at the time when they were published. Not only that, but they also present legal situations with the involvement of graduates or, frequently, even of lawyers already established. There are several angles in which he appears: sometimes as the main character, acting as the narrator of the plot. By the exposed, as the main goal, this paper proposes an analysis from the point of view of the character privileged by the legal environment on the three short stories chosen from the referred author. The main methodological approach for this study is the theoretical research, based on a bibliographical reference. Under this assumption, we perform an overview on the theoretical framework, in special when regarding the narrative texts selected for analysis. Concerning the main researchers for research and grounding, it is worth to stand out Gustavo Tadeu Alkmim (2008) and Roberto Schwarz (1988) concerning the plurality of the themes found in the Machadian plots; Antonio Candido (1977), Alfredo Bosi (2002), Leonardo Affonso Pereira (1968), Miguel Matos and Cassio Schubsky (2008) on the biography and different activities to which the author was dedicated; Sergio Buarque de Holanda (1936), Alfredo Bosi (2007), °At-is Borges Filho (2007), Marisa Gama-Khalil (2008) and Valdeci Rezende Borges (2000 and 2007) to talk about the city of Rio de Janeiro at the time of Machado and as an observational material for his writings; Nadia Battella Gotlib (1985) and John Gledson (2005) about the chronicler face of the author; Jose Wanderley Kozima (1996), besides Miguel Matos and Cassio Schubsky (2008) once again, to mention the presence of the legal world also in Machado's life; Gustavo Tadeu Alkmim (2008) one more time and Luiz Carlso Cancellier de Olivo (2007) regarding the Mark Law in the literary production of "Bruxo do Cosme Velho"; Roberto Schwarz (1990), Gilberto Freyre (2006), Beth Brait (1985), Oswald Ducrot and Tzvetan Todorov (1972), Massaud Moises (1992) and Aristotle (s/d) with respect to the character and also the construction of the Machadian interpreters; Antonio Candido (2011), Ligia Chiappini Leite (1985) and Therezinha Mucci Xavier (1986) for the analysis of the short story "Virginius (narrativa de urn advogado)"; Antonio Dimas (1985) and Rodrigo de Avelar Breunig (2006) in regard to the understanding of "Ex Cathedra"; Ana Helena Armange (2014) and once more the authors Nadia Battella Gotlib (1985) and Marisa Gama-Khalil (2008) for the work with the narrative "Suje-se Gordo!", among a series of other authors studied, classic and contemporary.
The caracyer constitution privileged by the legal environment in Machado de Assis short stories
Keywords: Machado de Assis; Conto; Personagem; Direito; Machado de Assis; Short story; Character; Law; LINGUISTICA, LETRAS E ARTES::LINGUISTICA